River life and the upspring of nature - Khan, Naveeda Ahmed, 1969- (Durham : Duke University Press, 2023)
"Naveeda Khan's River Life and the Uprising of Nature refigures the relationship between nature and culture through the study of chauras, or people who live on the chars (sandbars) within the Jamuna River in Bangladesh. Based on fieldwork largely conducted between 2011 and 2015, the book explores how nature acts a dynamic force that creates culture and impacts the human mind, body, and desire. The ethnography shows how alluvial flood plains give rise to certain social, political, spiritual, and familiar forms of life and reveals how nature inhabits humans and their prospects for social life. Khan argues that chaura lives are configured by nature and that nature makes persons and cultures in this place"--
River Life and Death -- Moving Lands in the Skein of Property and Kin Relations -- History and Morality between Floods and Erosion -- Elections on Sandbars and the Remembered Village -- Decay of the River and of Memory -- Death of Children and the Eruption of Myths -- The Chars in Recent Years.
Includes bibliographical references and index.
ESS
Keywords: Human ecology -- Bangladesh -- Jamuna River; Rural poor -- Bangladesh -- Jamuna River; Sand bars -- Bangladesh -- Jamuna River; River settlements -- Bangladesh -- Jamuna River